2015
DOI: 10.5489/cuaj.2708
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical bacillus Calmette-Guérin versus chemohyperthermia for high-risk non-muscle-invasive bladder cancer

Abstract: Introduction: Patients with high-risk non-muscle invasive bladder cancer (NMIBC) need adjuvant intravesical treatment after surgery. Although bacillus Calmette-Guérin (BCG) is highly effective, new adjuvant treatments to decrease recurrences and toxicity have been studies. We performed a retrospective propensity score-matched study to compare the efficacy of BCG and chemohyperthermia (C-HT). Methods: We included 1937 patients diagnosed with bladder cancer between January 2004 and January 2014. The primary effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 18 publications
2
26
0
Order By: Relevance
“…Bladder spasms tend to occur more frequently with neoadjuvant treatment (17.8 vs 10.7%; p = 0.398) [1]. Similar results were seen with BWT TM [70,73] and Combat TM [69,84] recirculant systems. Side effects are frequent, but almost all cases were grades 1 and 2.…”
Section: Cht Adverse Eventssupporting
confidence: 63%
See 2 more Smart Citations
“…Bladder spasms tend to occur more frequently with neoadjuvant treatment (17.8 vs 10.7%; p = 0.398) [1]. Similar results were seen with BWT TM [70,73] and Combat TM [69,84] recirculant systems. Side effects are frequent, but almost all cases were grades 1 and 2.…”
Section: Cht Adverse Eventssupporting
confidence: 63%
“…However, Ekin et al [70] showed that the recurrence-free rates of high-risk patients treated with BWT recirculant CHT were 82 and 61% at 1 and 2 years of follow-up…”
Section: Clinical Outcomes: Tumoral Recurrencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this technique seems less complex than RF-ChHT, current evidence for its efficacy is limited. Only five explorative studies using two different devices have been published, showing a 2-year RFS rate in intermediate-high risk NMIBC patients of up to 88% in the adjuvant setting [9][10][11][12][13]. No comparison has been made with MMC or BCG therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Another clinical paper [65] comparing the use of a heated MMC solution to the use of BCG, concluded that the Recurrence Free Survival (RFS) was significantly improved with the administration of BCG. In comparison, the recent paper on a multicentric, Randomized Controlled Trial of RITE vs. BCG in first line [66] showed a statistically significant superiority of RF+MMC over BCG in terms of RFS (81.8% vs. 64.8% in the PP, p=0.02).…”
Section: History Of Ritementioning
confidence: 99%